2002
DOI: 10.1016/s0014-5793(02)02370-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐cell signaling by direct contact increases cell proliferation via a PI3K‐dependent signal

Abstract: We report a novel mechanism of cellular growth control. Increasing the density of endothelial or smooth muscle cells in culture increased cell-cell contact and decreased cell spreading, leading to growth arrest. Using a new method to independently control cell-cell contact and cell spreading, we found that introducing cell-cell contact positively regulates proliferation, but that contact-mediated proliferation can be masked by changes in cell spreading: Round cells with many contacts proliferated less than spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
197
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(212 citation statements)
references
References 27 publications
12
197
0
3
Order By: Relevance
“…This increase in P-Akt in HME was only partially blocked by LY, although the levels of P-Akt in HME appeared to be decreased more than in HMC also regulates cadherin-mediated adhesions, which might be modulated by shuttling of p85. Nelson and Chen reported that Pi3K activity is required for cellcell contact induced proliferation, which is in line with our results [17].…”
Section: Discussionsupporting
confidence: 93%
“…This increase in P-Akt in HME was only partially blocked by LY, although the levels of P-Akt in HME appeared to be decreased more than in HMC also regulates cadherin-mediated adhesions, which might be modulated by shuttling of p85. Nelson and Chen reported that Pi3K activity is required for cellcell contact induced proliferation, which is in line with our results [17].…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with a recent report showing that cell-cell contact increases cell proliferation through a PI 3-K dependent signal. 41 Thus, R-Ras activates PI 3-K, and this activity induces cell cycle progression, which favors the increased growth of tumors in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Substrates composed of bowtie-shaped microwells of agarose on glass (750 m 2 /half bowtie) were fabricated as described previously (Nelson and Chen, 2002). Briefly, masters of patterned SU-8 photoresist (MicroChem, Newton, MA) were prepared by conventional photolithography.…”
Section: Fabrication Of Substrates With Microwellsmentioning
confidence: 99%